Mobile learning scenarios in language teaching: perceptions of vocational and professional education students - Nobre, Ana (2018)
Mobile devices play a significant role in society, in general, and a very limited one at the different levels of education. Smartphones, tablets, and other mobile devices allows learning to occur anywhere, (and at) anytime. These powerful technological devices can enhance the teaching and learning processes by helping to promote collaborative and individual learning and broadening the boundaries of the classroom to different contexts of learning. Many students have mobile devices and their applications can provide access to learning outside the classroom, for greater flexibility and more dynamic learning. In this sense, the articulation of technological and methodological efforts allowed us to create learning scenarios supported by the devices that students take to the classroom (BYOD), and use them to motivate and involve students in meaningful learning. These devices offer the advantage of integrating various technologies in the curricular contents, such as in foreign and mother language courses, representing a set of possibilities of ubiquity that can have great impact on the learning process. Thus, we developed strategies with vocational and educational students’ methodologies, such as augmented reality, project-based learning, game-based learning, collaborative learning and gamification. In this text, we present the results of two mobile learning studies in teaching French as a foreign language (to 18-23 year-old-students) and Portuguese language, as a mother tongue (to 15-19 year-old-students), in vocational education, implemented as a mediation tool in education to promote the construction of learning and development of significant skills of collaborative work. From the data collection, through a questionnaire, with open and closed questions, we highlight the favorable perception of the students to the integration of mobile devices in learning, and the recognition of the benefits of the teaching strategies used throughout the year, in the increase of curricular learning.